2017
DOI: 10.3892/mco.2017.1368
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum anti-p53 antibody expression following curative surgery for colorectal cancer

Abstract: Abstract. The aim of the present study was to investigate the usefulness of serum anti-p53 antibody (Ap53Ab) measurement for the diagnosis of colorectal cancer (CRC), and the clinical significance of the association between Ap53Ab expression and survival rate. Ap53Ab, carcinoembryonic antigen (CEA) and carbohydrate antigen (CA)19-9 were measured by ELISA in 674 CRC patients and 115 healthy volunteers (control group). The half-life time of Ap53Ab and CEA was calculated. The association between positive Ap53Ab e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Unfortunately, there are no data on reactivity with NFAs. While the half‐life of CEA in blood is reported to be 4‐12 days, the rate of decrease in serum CEA levels in our case was clearly faster than that. Although the half‐life times of NFAs are unknown, this finding suggests the possibility of the involvement of NFAs in serum CEA elevation if the EIA kits show cross‐reactivity with NFAs.…”
Section: Discussioncontrasting
confidence: 60%
“…Unfortunately, there are no data on reactivity with NFAs. While the half‐life of CEA in blood is reported to be 4‐12 days, the rate of decrease in serum CEA levels in our case was clearly faster than that. Although the half‐life times of NFAs are unknown, this finding suggests the possibility of the involvement of NFAs in serum CEA elevation if the EIA kits show cross‐reactivity with NFAs.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, the reference lists of review articles and related articles were manually screened to identify additional studies. Finally, a total of 80 articles involving 145 specific tumour‐associated autoantibodies detected in patients with CRC were selected (Table ) . Anti‐p53 antibody was the most commonly studied autoantibody, followed by MUC1, CEA, c‐myc, survivin, HDAC5, p62, ANXA4, koc, NY‐CO‐16, NY‐ESO‐1, RPH3AL, cyclin B, Imp1, IMPDH2 and MAGEA3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in order to further explore the potential diagnostic efficacy of autoantibodies, we performed a meta‐analysis of studies that assessed the diagnostic relevance of p53 autoantibody for CRC. After exclusion of 14 studies in which the blood samples were not collected before initiation of treatment (Table ), 27 studies published in 24 articles mentioning anti‐p53 were included in the meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The value in each sample was determined by comparing the optical density of the sample to that of the anti-p53 standard. The cut-off value was 1.3 U/ml, according to a previous colorectal cancer study (11,14). The carcinoembryonic antigen (CEA) levels were measured using a CEA-2 enzyme immune assay (EIA) kit (Elecsys CEAII; Roche Diagnostics K.K., Tokyo, Japan), following the manufacturer's instructions with a cut-off value of 5.0 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The usefulness of measuring serum anti-p53 Antibodies (Abs) in various malignant tumors has been suggested (6)(7)(8)(9). Compared to conventional tumor markers, anti-p53 Abs is useful for detecting early colorectal cancer (10)(11)(12). Yoshizawa et al reported the usefulness of measuring serum anti-p53 Abs in CAC in 2007 (13), which constituted this assessment eligible for health insurance coverage in Japan during that same year.…”
mentioning
confidence: 99%